Sinergy of The Judicial Commission and The Supreme Court in an Effort to Realize Professional Supervision of Judges - Shadiq, Amil (Manunggal Halim Jaya, 2025)
Oversight of judges is a vital element in maintaining the integrity and accountability of the judiciary. In Indonesia, this function is carried out by two main institutions: the Judicial Commission (KY) as an external supervisor and the Supreme Court (MA) as an internal supervisor. Despite their different mandates and approaches, synergy between the KY and MA is an absolute prerequisite for the realization of a clean, professional, and trustworthy judicial system. This article examines the forms of synergy that can be built between the two institutions, ranging from information exchange, the establishment of coordination forums, to the use of digital technology in oversight. Furthermore, it discusses the challenges of coordination, differing perceptions of authority, and the importance of political support and sustainable institutional reform. Effective oversight is not only repressive, but also preventive and educational, with the aim of building a culture of integrity within the judiciary. With a collaborative and adaptive approach, the KY and MA can become driving forces for the transformation of Indonesia's judicial system toward a dignified and substantive justice system.